Updates in Advanced Lithography - Hosaka, Sumio (IntechOpen, 2013)
Advanced lithography grows up to several fields such as nano-lithography, micro electro-mechanical system (MEMS) and nano-phonics, etc. Nano-lithography reaches to 20 nm size in advanced electron device. Consequently, we have to study and develop true single nanometer size lithography. One of the solutions is to study a fusion of top down and bottom up technologies such as EB drawing and self-assembly with block copolymer. In MEMS and nano-photonics, 3 dimensional structures are needed to achieve some functions in the devices for the applications. Their formation are done by several methods such as colloid lithography, stereo-lithography, dry etching, sputtering, deposition, etc. This book covers a wide area regarding nano-lithography, nano structure and 3-dimensional structure, and introduces readers to the methods, methodology and its applications.